Pengaruh Konten Instagram @Ngopibarengbaradjawa terhadap Minat Beli Followers - Oktaviona, Annisa Maurin; Bungin, Burhan (Journal of Management and Bussines (JOMB), 2026)
This research aims to measure the influence of Instagram content on the buying interest of followers of the @ngopibarengbaradjawa account, a coffee shop located in Surabaya. In the context of social media, Instagram has a strategic role in product marketing through unique and interesting visual content. This research uses the Hierarchy of Effect and AIDA models to analyze how Instagram content influences consumer behavior, from attention to purchasing actions. The research method used was quantitative by distributing questionnaires to 171 respondents, who were followers of the @ngopibarengbaradjawa account. Data were analyzed using Pearson Product Moment correlation to test the relationship between Instagram content variables and purchase interest. The research results show that there is a very significant correlation between Instagram content and followers' buying interest. A Pearson correlation of 0.984 indicates a strong relationship between these variables. Thus, interesting Instagram content can effectively influence consumer purchasing interest, especially in the context of marketing beverage products on social media.   Keywords: Instagram Content, Purchase Interest, Followers